Improvement of dielectric strength and properties of cross-linked polyethylene using nano filler - Sherif Essawi; Loai Nasrat; Hanafy Ismail; Jeannette Asaad (Institute of Advanced Engineering and Science, 2022)
Power cables insulated with cross-linked polyethylene (XLPE) have been utilized worldwide for distribution and transmission networks. There are several advantages for this type of insulation; it has better electrical, thermal, and mechanical properties compared to other types of insulation in medium and high voltage networks. Many studies aimed to improve the XLPE characteristics through introducing nano fillers to the XLPE matrix. Therefore, this paper investigates the AC (HV) breakdown voltage (dielectric strength) of XLPE after adding nano-sized zeolite (Z) fillers with various concentrations of 1 wt%, 3 wt%, 5 wt% and 7 wt%. The dielectric strength is tested in different temperatures of 30 ⁰C and 250 ⁰C. Additionally, it was tested in low and high salty wet conditions. The dielectric strength of the XLPE has been enhanced by inducing the Z nano filler. The results of the tests were used to train the artificial neural network (ANN) to calculate the dielectric strength of XLPE composites with different concentrations of nano Z filler under different weathering conditions. Thermogravimetric analysis, tensile strength, and elongation at break tests were applied to check the thermal and mechanical characteristics of the samples. Experimental findings show that the optimum concentration of nano Z is 3.64 wt% to enhance the electrical, thermal, and mechanical properties.